Documentation of floral secretory glands in Pleurothallidinae (Orchidaceae) using Scanning Electron Microscopy (SEM) - Karremans Lok, Adam Philip (2016)
A clear, step by step description of the treatment of orchid flowers, subtribe Pleurothallidinae, with Critical Point Drying for SEM is presented. It shows that a simple, short fixation and dehydration method prior to Critical Point Drying is sufficient to obtain good results.